Bilateral Facial Palsy Due to Granulomatosis with Polyangiitis: A Case Report - Shil, Rajish Sanjit Kumar; Teir, Jamal Ali (Current Innovations in Medicine and Medical Science Vol. 3, 2022)
Granulomatosis with Polyangiitis (previously known as Wegener's granulomatosis) is a systemic autoimmune disease that can cause necrotizing vasculitis in small vessels and inflammation of blood vessels in the nose, sinuses, throat, lungs, and kidneys. In rare cases, it has been shown to involve the brain and cranial nerves as well. The objective of this study is about identifying and investigating for the causes of facial palsy, in order to initiate appropriate treatment strategy for secondary causes. We describe a case of granulomatosis with polyangiitis that was worsened by bilateral facial palsy brought on by lower motor neuron involvement of the facial nerve and that had a good response to immunosuppressive therapy. As this technique might effect the patient morbidity and mortality on early illness therapy, it is prudent to be alert in studying individuals with atypical systemic autoimmune disease presentations.